Carta de Roberto H. Todd al Coronel G. H. Estes - Estes, G. H.; Todd, Roberto H. (My University, 1926)
Carta relacionada a campamentos de entrenamiento para oficiales de color.
Keywords: Estes, G. H.--Correspondence.; Estes, G. H.--Correspondencia.; Todd, Roberto H.--Correspondence.; Todd, Roberto H.--Correspondencia.